Viologens: a versatile organic molecule for energy storage applications. Issue 48 (30th November 2021) - Kathiresan, Murugavel; Ambrose, Bebin; Angulakshmi, Natarajan; Mathew, Deepa Elizabeth; Sujatha, Dhavamani; Stephan, Arul Manuel
Abstract : This review analyses the role of viologens, a unique class of redox-active molecules in various energy storage devices and the nature of chemical interactions in enhancing their overall performances. Abstract : Organic redox compounds are a fascinating class of active materials used in energy storage applications. The structural diversity as well as ability to be molecularly tailored assists in fine-tuning of their electrochemical properties at the molecular level, which is highly desired for performance improvement. In reality, it is very challenging to achieve the desired physicochemical properties. Viologens represent a unique class of redox-active molecules that undergo two one-electron reductions in steps. Their redox properties have been highly explored in various fields such as electrocatalysis, electrochromism, photochromism, herbicides, and to some extent in energy storage systems. Their redox behavior as well as cationic charges are highly useful for improving device performance in energy storage systems. Different energy systems require different states of viologens, i.e., dicationic, monocation radical, or redox couple. For example, viologen dication shows electrostatic attraction towards polysulfides in Li–S batteries, and similarly, dication radical prevents Li dendrite growth in Li-ion batteries. In the case of redox flow batteries, such as supercapacitors and Li–air batteries, the redox behavior of viologens is useful for improving the performance. Despite these advantages, there are some challenges existing in viologen-based systems that must be conquered at the molecular level. In this regard, a systematic study on structure–activity relationships becomes crucial to address the bottlenecks. This review comprehensively analyses the role of viologens in various energy storage systems and the mode of chemical interactions responsible for enhancing the overall performance of electrochemical storage devices.